Antarctophthirus trichechi Bohemann 1865 ... - Leonardi, Maria Soledad; Palma, Ricardo Luis (Zenodo, 2013)
Antarctophthirus trichechi (Bohemann, 1865) Haematopinus Trichechi Bohemann, 1865: 577, pl. 35, figs 2, 2a,b. Haematopinus trichechi Bohemann, 1865; Piaget 1880: 656; Breddin 1901: 557; King 1964: 139. Haematopinus tricheci [sic] Bohemann, 1865; Dalla Torre 1908: 11. Misspelling. Antarctophthirus trichechi (Bohemann, 1865); Enderlein 1909: 508, 512, pls 55–56, pl. 60, figs 185–188; Neumann 1909: 532, figs 30–31; Kellogg & Ferris 1915: 49, fig. 17B, pl. 3, fig. 1; Ferris 1916a: 183; Cummings 1916: 172; Fahrenholz 1917: 5; Freund 1928: 25, figs 24–29; Ferris 1934: 492, figs 287–288; Maltbaek 1937: 20; Thompson 1938: 94; Herms 1939: 105; Eichler 1941: 375, fig. 34; Hopkins 1949: 509; Weber 1950: 172; Ferris 1951: 75; Blagoveshtchensky 1958: 377; Scherf 1963: 17, figs 1–6, 19–20; Blagoveshtchensky 1964: 326; King 1964: 139; Spencer 1966: 23; Margolis & Dailey 1972: 14; Kaisila 1973: 64; Kim et al. 1975: 547; King 1983: 203; Kim et al. 1986: 48, pl. 3; Zarubina 1986: 373; Kim 1988: 108; Durden & ... : Published as part of Leonardi, Maria Soledad & Palma, Ricardo Luis, 2013, Review of the systematics, biology and ecology of lice from pinnipeds and river otters (Insecta: Phthiraptera: Anoplura: Echinophthiriidae), pp. 445-466 in Zootaxa 3630 (3) on page 449, DOI: 10.11646/zootaxa.3630.3.3, http://zenodo.org/record/221768 ...